TERT Promoter Mutation Predicts Radioiodine-Refractory Character in Distant Metastatic Differentiated Thyroid Cancer - Yang, Xue; Li, Jiao; Li, Xiaoyi; Liang, Zhiyong; Gao, Wen; Liang, Jun; Cheng, Shujun; Lin, Yansong (Journal of Nuclear Medicine, 2017)
Telomerase reverse transcriptase (TERT) promoter mutation has been reported to be associated with aggressive characteristics in differentiated thyroid cancer (DTC). This study examined the status of TERT mutation in distant metastatic DTC and evaluated the correlation between TERT mutation and radioiodine uptake, as well as that between TERT mutation and therapy response. TERT promoter and B-Raf proto-oncogene (BRAF) V600E mutation were retrospectively examined in primary tumors of 66 patients with distant metastatic DTC. Stimulated thyroglobulin (sTg) changes, radioiodine uptake status (avid or nonavid), and other imaging evidence were analyzed to evaluate therapy response. After a median follow-up of 46.5 mo (interquartile range, 29.0-70.5 mo), therapy response was classified as either disease control or refractory. The prevalence of TERT mutations was 22.73% (15/66), of which C228T mutation was more prevalent (13/15) than C250T mutation (2/15). Rising sTg was noticed in 93.33% (14/15) of the TERT mutation group. Of cases negative for both mutations, 78.12% (25/32) presented with decreased sTg. TERT mutation closely correlated with a poor response to radioiodine therapy (P < 0.001), and all 15 patients were classified as refractory to radioiodine therapy, with a positive predictive value of 100% at the endpoint of follow-up. TERT mutation was associated with older mean age at diagnosis (P < 0.001), larger mean tumor diameter (P = 0.013), and greater likelihood of both BRAF mutation coexistence (P = 0.044) and radioiodine-refractory character (P < 0.001). In the 36 cases whose imaging results underwent semiquantitative analysis, TERT mutation significantly correlated with non-radioiodine avidity, with a much lower mean tumor-to-background ratio (obtained from postradioiodine whole-body scanning) than in TERT wild-type cases (P < 0.001). In addition, patients with distant metastatic DTC with TERT mutation were more likely to lose radioiodine avidity at the initial radioiodine therapy than were those with only BRAF mutation (8/8 vs. 5/11; Fisher exact test, P = 0.018). TERT mutation closely associates with non-radioiodine avidity in distant metastatic DTC, and when compared with BRAF mutation, TERT mutation manifested a greater negative influence on radioiodine uptake. TERT mutation could also be used as an early predictor of radioiodine-refractory cases.